Caracterização molecular, morfofisiológica e fitoquímica de Varronia curassavica do Sul do Espírito Santo - Grancieri, Natália (2015)
The use of plants for medicinal purposes is one of the oldest forms of medical practice of mankind. In Brazil, the consumption of plants for medicinal purposes and in herbal medicines is increasing in all social classes and has received various incentives. To optimize the use of medicinal plants become important studies on genetic variability, as it has done the genetic and breeding programs trying to select superior genotypes. This requires performing their characterization using descriptors such as agronomic, morphological, biochemical and molecular. One of the concerns is the uniform production of secondary metabolites and understand the factors that can influence it. Among the various species of medicinal plants known in Brazil, is the curassavica Varronia, which despite its pharmacological and economic potential, yet little is known about their genetic diversity of natural populations. Thus, this study aimed to characterize genotypes of different native peoples of southern Espirito Santo, with variations of altitude, and thus compare them with pre-improved materials purchased from the State University of Campinas (Unicamp). Were collected from each plant, branches to be held vegetative propagation. The seedlings were grown in a greenhouse and then conducted molecular analyzes, physiological, morphological and physiological and phytochemical. It was found that in this experiment was low experimental precision. According to an estimated variation index (VI), there are variables that can be used to genotype selection. The heritability of most variables were medium to high. In clusters the variables of greater relative contribution were: AFT, SLA, LAI, FLA, CLT, CAB, A, gs, A / gs. A new grouping based on nine variables of relative contribution and so were formed three groups, the AFT being, AFE and the FLA that had the greatest contribution to the genetic divergence was conducted. When compared this group to the grouping performed by molecular markers, there was no identical or similar groups. In clusters, the genotypes are not grouped based on local collections of close or similar altitudes.